Hematological Profile in Free-Range Chickens at The Age Of 4, 8, 12 Weeks - Horhoruw, Wiesje; Kewilaa, Arnold Ismael (Sahabat Publikasi, 2024)
The purpose of this study was to determine the hematological profile in hens at the ages of 4, 8, and 12 weeks. The research lasted for 4 months, and its implementation was in the Laboratory of the Department of Animal Husbandry, Faculty of Agriculture, Pattimura University. The livestock commodities used in this study were native chickens in the age groups of 4, 8, and 12 weeks. Each age group will have 4 pieces of blood drawn. The variables observed are hematological values, namely the number of erythrocytes, hemoglobin levels, and hematocrit values. The results showed that the age of native chickens had a significant effect on hematocrit values and hemoglobin levels, while the average number of erythrocytes did not differ markedly. The average number of erythrocytes, hematocrit values, and hemoglobin levels of native chickens at the ages of 4, 8, and 12 are still within the normal range.